Task Types in EFL Listening Class: Realizing Learners’ Prospects - Nurita, Nurita (Universitas Muhammadiyah Jember, 2017)
Selection of task types in learning listening certainly affects the quality oflearners’ necessities. The seven types of tasks offered by Willis (2007) are oftennot simply applicable because different class characteristics always presentdifferent burdens in determining the right types of task. The goal of this studyis to describe learners’ prospect of task types in teaching listening skill at EFLclass for university students. A listening class consisting of thirty students whichhad experienced different task types in four years was chosen. To achieve theobjective, the researchers collected the data by observing the teaching learningprocess and interviewing both the teacher and the learners. The result of dataanalysis revealed that there were four types of task implemented in the listeningclass, those were; listing task, sharing personal experience task, comparingtask and creative task. The class used listing task by asking the learners tomention the information they have got from the short video. Comparing taskwas implemented by asking the learners to match the information betweenthe video and what they have got. In sharing personal task, the class askedthe learners about their personal experience that was related to the discussedmaterial. The last was creative task in that learners were to find their own videoabout the topic they have decided and asked the learners to present their videoin front of class by telling the audience about the content of the video. In short,the final end of employing task types is on helping learners grasp their learningprospects so in designing the task types the class has to stick to the objective ofthe task, the materials and level of difficulty and the learners’ capability.